Estudo da adsorção de etileno em filmes compósitos de quitosana e zeólita - Sousa, Suliene Dantas do Nascimento (2016)
Brazil produces more than 43 million tons of fruit per year, 47% of which is sold as fresh fruit and only 2% is destined for export. Aiming to increase this export, it was studied the production of chitosan and zeolite films that could adsorb the ethylene liberated by the fruits, which is one of the main factors that accelerates the metabolic activity and anticipate the aging of the fruit. Biodegradable films based on chitosan, which have important characteristics such as antibacterial and antifungal, have the support function of the zeolites that are molecular sieves capable of adsorbing ethylene, delaying the ripening of the fruits, reducing the waste and can facilitate the export. Dense and porous composite matrices were developed, differing their porosity by the drying process. Zeolite and composite matrices were characterized as their texture properties using nitrogen and carbon dioxide, scanning electron microscopy (SEM), water vapor permeability (PVA), and their ethylene adsorption capacity. The zeolite presented different porosity and surface area, using adsorption of N2 at -196ºC, or with CO2 at 0ºC, due to the low diffusion of N2 in molecular sieves. SEM showed a uniform distribution of zeolite in the polymer matrix and the appearance of pores from the lyophilization procedure. The chitosan film with 93% (m m-1) of zeolite (QZ93) had a lower adsorption capacity than the film of the same concentration that was lyophilized (QZ93Lio), because of the higher porosity, this presented adsorption value similar to Regenerated zeolite 90 ° C (ZR 90). The films of pure chitosan (Qtra), chitosan with 33% zeolite (m m-1) (QZ33) and lyophilized pure chitosan (QLio) present small amounts of adsorbed ethylene compared to other materials. All materials were able to adsorb ethylene. Its application seems quite feasible since the market value for these materials is more accessible than other adsorbents used and should be studied taking into account the amount of ethylene released by the fruit to be transported, whether or not it is necessary to use the material Which adsorbs greater amounts of ethylene.